Down Syndrome: Development Of A Non-Invasive Prenatal Dna Screening Test Using Superoxide Dismutase 1 Gene In Maternal Blood And Detection Of Cystathionine P-Synthase Gene Mutations - Karuppiah, Thilakavathy (2004)
Down syndrome or Trisomy 21, is the most commonly occurring genetic disorder that stems from the failure of ·chromosome 21 to segregate normally during meiosis, resulting in an individual carrying an extra copy of chromosome 21. The main aims of this study were to develop a relatively non-invasive prenatal DNA screening method using maternal blood and to detect mutations on cystathionine J3-synthase (CBS) gene, a folate pathway gene located on chromosome 21. As an initial step, the presence of foetal cells and DNA in the maternal blood was firstly determined by foetal haemoglobin (HbF) staining and polymerase chain reaction (PeR). It was found that the ratio ofthe nucleated foetal cell to maternal cell increased from 2 in 106 to 3 in 106 and 5 in 106 at the first, second and third trimester, respectively. By using Y chromosome specific primers, DNA from male foetuses could be detected as early as 6 weeks of gestation in 200 Jil maternal blood obtained from fingertip. This is in line with the current technology in non-invasive screening methods of foetal aneuploidies which is focused on detecting Y chromosomal sequences which is impossible to be used for female foetus pregnancies. Therefore, the superoxide dismutase 1 (SOD'!) gene sequence, which is located on the Down Syndrome Critical Region, was used to overcome this situation by using real-time quantitative PCR The level of SOD1 sequences in maternal blood was found to be significantly elevated in the third trimester normal pregnancies (mean = 11728 copies/Ill) when compared to the second trimester (mean = 5705.6 copies/Ill), p<0.OO5 and non-pregnant normal women (mean = 3580.2 copies/Ill), p<O.OOOl. Down syndrome pregnancies have the greatest elevation compared to all the three trimesters of normal singleton pregnancies and twin pregnancies,p<0.05. The traditional approach ofprenatal chromosomal diagnosis using amniotic fluid was found to be cumbersome and time-consuming compared to the newly developed method. The mutation detection on CBS gene was carried out using DNA sequencer and denaturing high performance liquid chromatography (DHPLC). This study revealed that the Down syndrome patients have four mutations, which are in intron 1 (A9231C), exon 10 (C20628T) and exon 17 (T277%C and C27817T). The Down syndrome children were found to have the same genotype as their mothers. The number ofmothers and children having the substitutions in the CBS gene was twice the number ofmothers and children with normal genotype, suggesting that the mothers who have these substitutions are at higher risk of having a child with Down syndrome. In conclusion, non-invasive prenatal diagnosis at first trimester using Y chromosomal sequence IS feasible for diagnosis of foetal-derived paternally-inherited polymorphism/mutations or genes. Quantitative analysis using gene associated with a disorder has a potentially significant advantage over the invasive techniques currently used widely for prenatal diagnosis. Finally, the discovery of the mutations in the CBS gene of Down syndrome patients and mothers will help contribute to new knowledge and the future studies on the folate pathway genes mutation and occurrence of Down syndrome. It may also suggest an opportunity to improve public health strategies for the primary prevention ofDown syndrome